2019
DOI: 10.1021/acs.jpca.9b00879
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Excited-State Intramolecular Proton Transfer Mechanisms of Two Novel 3-Hydroxyflavone-Based Chromophores in Two Different Surroundings

Abstract: The dynamic excited-state intramolecular proton transfer (ESIPT) mechanisms of two novel 3-hydroxyflavone-based chromophores (1 and 2) in different surroundings (nonpolar cyclohexane and polar acetonitrile solvents), which are reported in the recent work (Chou et al. J. Phys. Chem. A. 2010, 114, 10412), are explored in terms of the density functional theory (DFT) and time-dependent DFT theoretical methods. The computational absorption and emission spectra for the work rendered here were in reasonable agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…In water, we detect a constant red-shift of 160 cm À1 for ν O11 H from N to N*, while more significant red-shift energy of 200-214 cm À1 is found for benzene, which is equal to lower energy of about 0.45-0.57 kcal/mol. This result agrees with previous studies for various OH-containing molecules, such as 4-dimethylaminoflavonol [84] or 3-hydroxy flavone-based chromophores [34].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In water, we detect a constant red-shift of 160 cm À1 for ν O11 H from N to N*, while more significant red-shift energy of 200-214 cm À1 is found for benzene, which is equal to lower energy of about 0.45-0.57 kcal/mol. This result agrees with previous studies for various OH-containing molecules, such as 4-dimethylaminoflavonol [84] or 3-hydroxy flavone-based chromophores [34].…”
supporting
confidence: 93%
“…The spectroscopic research of the same groups revealed that the emissions of MFOH are easily modulated in hydrocarbon solvents [28], alcoholic solvents [29], weakly aprotic [30,31], and binary mixture solvents [32]. Recently, many authors employed theoretical tools to study the solvent-dependent ESIPT and reported that non-polar solvent is a supportive medium for the ESIPT mechanism because of no solvent perturbation [33,34]. In addition, Peng et al showed that the ESIPT mechanism is inhibited for 1,2-dihydroxyanthraquinone derivatives by the protic solvent (water/methanol); in that medium, only the enol emission is observed [35].…”
mentioning
confidence: 99%
“…It is noteworthy that the fluorescence spectral characteristic of DHPOD fibers with double fluorescence emission has also appeared in many excited-state intramolecular proton transfer (ESIPT) molecules whose molecular structures contain intramolecular hydrogen bonds between heterocycles and phenolic hydroxyl groups. [21][22][23][24][25][26][27][28][29][30][31][32] Thus, as similar as ESIPT molecules documented before, DHPOD macromolecules may undergo an ESIPT reaction as well. As depicted in Figure 4b, upon ultraviolet light excitation, the enol tautomer (S 0 ) transits to its first excited state (S 1 ).…”
Section: Uv Resistance Mechanism Of Dhpod Fibersmentioning
confidence: 88%
“…The excited-state intramolecular proton transfer (ESIPT) was first proposed by Weller, who used this mechanism to successfully explain the absorption spectra and double fluorescence spectra phenomena generated by methyl salicylate molecules. Since then, ESIPT has been extensively studied due to its special photophysical and photochemical properties. ESIPT refers to the proton-transfer process that occurs in excited-state molecules between the adjacent proton donor and proton acceptor upon photoexcitation. The ESIPT reaction is a four-step photoinduced tautomerism process.…”
Section: Introductionmentioning
confidence: 99%